A Brand Activation for Yummy for Tummy, Which Will Serve As an Educational Media Regarding GERD for Gen Z - Alexandra, Stephanie Giovanna (Jurnal Vicidi, 2024)
Yummy for Tummy is a brand that is focused on GERD related problems in Indonesia. What prompts this brand’s creation is the high GERD rate in Indonesia, yet the awareness regarding this is still worryingly low. To be able to contribute to solve the problems found by the brand, Yummy for Tummy decided to create a brand activation called ‘Your Healthy Buddy’. The research method used is both qualitative and quantitative methods. The qualitative method is done by researching credible books and journals, as well as by conducting interviews with extreme and expert users. While the quantitative method is done by sharing a survey with 51 respondents. The designs created for the brand activation consists of educational illustration, interactive challenge, interactive Instagram Story, Instagram Reels, and Merchandise. From the research, it can be concluded that with the existence of Your Healthy Buddy, it is expected that education regarding GERD in social media can increase and help provide impactful education for the people.